PENGARUH LIKUIDITAS, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Jesson; Hikmah, Hikmah (LPPM Universitas Putera Batam, 2025)
The rapid economic growth has led to the emergence of many new business entities, which in turn intensifies competition across various industrial sectors. As a result, companies focus on enhancing their firm value to remain competitive. This study aims to determine whether liquidity, profitability, and firm size significantly affect firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The population studied consists of 19 manufacturing companies in the textile and garment sector listed on the IDX, with a relevant sample of 11 companies. The research method employed is quantitative data collection using documentation techniques, relying on annual financial statements accessed from the official IDX website for the period 2019 to 2023. The research findings show that liquidity has a negative and significant effect on firm value, profitability does not have a significant effect, and firm size has a positive and significant effect on firm value in manufacturing companies in the textile and garment sector listed on the IDX during the period 2019-2023.